Miscibility and hydrolytic degradation in alkaline solution of poly( l-lactide) and poly( p-vinyl phenol) blends - Shirahase, Tomoko; Komatsu, Yoichi; Marubayashi, Hironori; Tominaga, Yoichi; Asai, Shigeo; Sumita, Masao (Polymer Degradation and Stability, 2007)
Poly( l-lactide) (PLLA) was melt-blended with poly( p-vinyl phenol) (PVPh) using a two-roll mill, and the miscibility between PLLA and PVPh and degradation of the blend films were investigated. It was found that PLLA/PVPh blend has miscibility in the amorphous state because only single T g was observed in the DSC and DMA measurements. The T g of the PLLA/PVPh blend could be controlled in the temperature range from 55 °C to 117 °C by changing the PVPh weight fraction. In alkaline solution, degradation rate of PLLA/PVPh blends was faster than that of neat PLLA because PVPh could dissolve in alkaline solution. The surface morphology of degraded PLLA and PLLA/PVPh blend were observed by SEM. The surface morphology of degraded PLLA/PVPh blend was finer than that of PLLA. Young's modulus of PLLA/PVPh blend increased with increasing PVPh content. Yield stress of PLLA/PVPh blends whose PVPh content was less than 30 wt% kept the level of about 55 MPa and that of PLLA/PVPh blend whose PVPh content was 40 wt% is much lower than that of neat PLLA.